Reconstruction of comminuted jaw with iliac crest graft and implant-supported prostheses – case report (Research, Society and Development, 2020)
Comminuted jaw fractures represent a challenge in terms of treatment. The advancement of fixation techniques and materials has contributed to the surgeon providing faster treatment and less complication. Even so, cases that present severe mandibular fragmentation require additional therapies, such as the use of bone grafts and dental implants, in order to recover function, aesthetics and anatomy of the mandible. This work aims to report a case of comminuted mandibular body fracture, which was treated with reconstruction, initially by rigid internal fixation, and secondly, by iliac bone graft and implant-supported oral rehabilitation. Although studies in the literature demonstrate that autogenous grafts show significant resorption, they are still considered the gold standard, and allow an ideal basis for obtaining osseointegration of dental implants. Thus, we concluded that the use of the autogenous bone graft coming from the iliac crest and rehabilitation with implants can be a satisfactory option for functional and aesthetic repair of patients who presented high impact fractures, and developed significant bone defects.